Heeding clues to metformin-associated lactic acidosis: prompt response can save life. Issue 8 (25th July 2008) - Kumar, U; Chennavir, B; Gopi, A
Abstract : The case history is presented of a patient who developed metformin-associated lactic acidosis. The patient made a complete recovery with supportive care. Recognition of metformin-associated lactic acidosis requires a high index of suspicion as presentation can be very subtle.